The theory and practise of legal feminism: examining its impact on the representation of women in Indonesia - Novita Alfiani; Nesita Anggraini (Journal of Law, Environmental and Justice, 2023)
This paper examines Indonesian legal feminist theory on public sector women representation. Data is collected and analyzed by observation in this sociological legal research. According to the findings, gender inequality underpins a variety of attitudes and activities that promote equal rights. Elizabeth Cady Stanton's feminism was founded on the conflict. The pursuit of rights requires active lobbying, which has sparked social change, mostly through new laws passed by governments. Feminist legal consciousness shapes legislation. However, legal culture appears to affect activists' different methods of communicating their goals. As pre-18th-century nations, Britain and America have faced political turbulence caused by feminists campaigning for women's suffrage. The UK addressed the matter by legislation, while the US changed the constitution. Contrary to Indonesia, where women's political rights were recognized later, equality was achieved by affirmative action laws to increase women's political representation. However, following socioeconomic shift also limited affirmative action implementation, hindering democratic progress.